PEMANFAATAN MEDIA DALAM PEMBELAJARAN BIOLOGI DI SEKOLAH - Amna Emda (Jurnal Ilmiah Didaktika, 2011)
In teaching learning process, teachers have to use some media of instruction. They have to be able to select appropriate media with the concept that they want to teach. In biology, especially the concept of biodiversity, the teacher should explain and introduce the students to various plants available around them including herb plants. It will be one of solution for a teacher to achieve an optimum goal if they can use the diverse plant around them. The successful of learning especially in the field of biology can be seen from cognitive, affective and psychomotoric aspects which is hoped to be achieved if the teachers as educators can guide their students to know about the plants in the field.